Bronnen voor liturgie-onderzoek. Voorbeelden van perspectiefverbreding - Evers, Johannes H. M. (Jaarboek voor liturgieonderzoek, 1989)
From several sides impulses and pleas have been given to open a wider perspective for historical and ethnological research. These impulses also have their meaning for the theological research of liturgy. Three adhortations are presented in particular. The wishes of a church-historian aim at the study of the way liturgy and piety had their impact on the daily-life of ordinary people. The history of mentalities tries to give a reconstruction of the thoughts, feelings and acts, using varied sources. Ethnology of religion and theological research of liturgy seem to have made a division in their common fields of research. But the ideology under this division is critisized and a plea is held for multi-disciplinarity and a revision of the borders between fields of research, in order to come to a more adequate study of the complex reality of the roles religion plays in the daily-life. In the second part of this article some examples are given of this new approach that opens a wider perspective for the theological research of liturgy, by using sources who are mostly neglected because of their so-called lack of theological substance and esthetical value. The examples are focused around one location: the centre of pilgrimage and devotion to Saint Gerard Majella, laybrother-Redemptorist (1726-1755), in Wittem (in the south of the Netherlands). 1. The first set of examples deals with the content of the offered pastoral forms. An analysis is made to give a systematic account of the religious concepts presented by the fathers to the visiting public in celebrations, songs, prayers, sermons, prayerbooks and a periodical. 2. The second set of examples gives an approach from liturgy and arts. Songs of devotion reveal religious concepts in a subjective, emotional atmosphere. The collection of churchmusic in combination with the notes of the conductors of the choir, is an indication for the churchmusical practice in a convent-church. The archives of the cloister contain precious songbooks. Investigations in archives are important not only for historians but also for liturgists. The architecture of the centre of pilgrimage has its own message and impact on the visitors. Changes in architecture (both outside and inside) indicate slow movements in the religious mentality of the leading persons and of the visitors. The iconografic scenes can be studied to discover various and conflicting functions, messages and developments. A hypothetical interpretation of the paintings on the walls and ceiling of the church gives an example of the possibilities of this approach. 3. Whereas the examples sofar presented reflect the religious concepts offered at the visitors, there are sources also for a description of the religious mentality of the fathers, who lived in the convent. A history of spirituality, that does not only give attention to some outstanding, spiritual gifted persons, may use autobiographic notes, necrologies and letters of fathers to construct an image of the religious life inside a convent. A third set of examples offers an illustration of the possibilities by using these sources. 4. The fourth set of examples is focused on the way people react upon and receive the offered pastoral forms. A tension can be discovered between the ideas of the fathers, presented in pastoral functions and the religious concepts of the visitors. These concepts have been thoroughly influenced by pastoral messages of former periods. The approach of the history of mentalities and the research on the reception of offered messages have connections and can both be used with success in order to develop a pastoral strategy for pilgrimage and piety in our days.The presented four ways of investigating a centre of pilgrimage put into practice the desired crossing of borders between scientific disciplines and provide complementary information both on the history of liturgy and piety as well on the functions this centre has nowadays. The division between the mainstream of official christian liturgy and the popular practices has caused a gap between theological research on liturgy and ethnology of religion. The study of the role religion plays in ordinary life brings these disciplines together, opens the field for cooperation with other disciplines and stresses the use of sources sofar neglected. The reflection on content and purpose of christian liturgy has to be completed and corrected by the research of the empirical presence and expression of religion nowadays and for the past. Maybe the necessary sources are rare or not inviting to theological investigation, but this is a bad excuse. Liturgical research serving pastoral sciences has to take in account the normative and official rituals, but may not let aside the lived liturgy of ordinary people in daily-life.